Kryptografie a moderní kryptografické algoritmy - Orság, Dominik (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2023)
Cílem této práce je poskytnout ucelený přehled o historickém vývoji kryptografie a důležitých kryptografických metodách současnosti. V teoretické části práce jsou nejprve popsány základní pojmy a historický vývoj kryptografických algoritmů. Dále jsou popsány moderní symetrické a asymetrické algoritmy. Největší pozornost je věnována algoritmu RSA a jeho implementaci v jazyce Python.

The goal of this bachelor thesis is to provide a comprehensive overview of the historical development of cryptography as well as important cryptographic methods of today. The theoretical section begins with an exploration of fundamental concepts and the historical progression of cryptographic algorithms. This is followed by a descroption of modern symmetric and asymmetric algorithms. The greatest attention is paid to the RSA algorithm and its implementation in the Python language.
Cryptography and modern cryptographic algorithms
Keywords: Kryptografie; šifrování; dešifrování; klíč; algoritmus; digitální podpis; RSA; DES; Cryptography; encryption; decryption; key; algorithm; digital signature; RSA; DES